Quality Analysis of Bonded Joints in the Renovation of Plastic Automotive Parts - Ján Varga; Janette Brezinová; Jakub Brezina (Applied Sciences, 2023)
In the field of automotive parts, bonded joints are finding more and more applications. One of the main advantages of these joints is their non-destructive bonding. Due to them being permanently applied and being exposed to external operating conditions, their strength properties are reduced, especially when it comes to parts forming the functional unit of a car after renovation. It is, therefore, important to be able to understand these influences, which can help us to understand the extent to which these plastic parts are affected by external operating conditions after renovation. This article shows the various influences that these plastic parts produced using bonding technology and what they can be exposed to. For the evaluation of bonded joints, the following environments simulate the operating condition: SO2 concentration at total moisture condensation, 20% salt solution, and exposure in atmospheric conditions for one year in the environment. The best values among MEGABOND 2000, ChS EPOXY, and DINITROL 860 adhesives are achieved by ChS EPOXY adhesive, which can be recommended for the renovation of plastic parts for the automotive industry.